2000
DOI: 10.1093/ajcn/71.6.1462
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones improve plasma lipids in normocholesterolemic, premenopausal women

Abstract: Background: Soy consumption is known to reduce plasma total cholesterol and LDL cholesterol in hypercholesterolemic subjects, but the responsible soy components and the effects in normocholesterolemic subjects remain unclear. Objective: The effects of soy isoflavone consumption on plasma total cholesterol, HDL-cholesterol, LDL-cholesterol, triacylglycerol, apolipoprotein A-I, apolipoprotein B, and lipoprotein(a) concentrations and on LDL peak particle diameter were examined in normocholesterolemic, premenopaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
2
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(125 citation statements)
references
References 49 publications
6
109
2
4
Order By: Relevance
“…Although the clinical characteristics of subjects in the present study may have contributed to the lack of change observed in plasma lipids, other dietary substances (such as soy protein) have been shown to improve plasma lipids in young normocholesterolemic subjects (Wong et al, 1998;Merz-Demlow et al, 2000;McVeigh et al, 2006). In addition, prospective studies have reported a relationship between lipid concentrations within the normal range and future CHD (Klag et al, 1993;Strandberg et al, 2004), and current public health recommendations suggest lower goals for optimal plasma lipid concentrations (Expert Panel, 2001;Grundy et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…Although the clinical characteristics of subjects in the present study may have contributed to the lack of change observed in plasma lipids, other dietary substances (such as soy protein) have been shown to improve plasma lipids in young normocholesterolemic subjects (Wong et al, 1998;Merz-Demlow et al, 2000;McVeigh et al, 2006). In addition, prospective studies have reported a relationship between lipid concentrations within the normal range and future CHD (Klag et al, 1993;Strandberg et al, 2004), and current public health recommendations suggest lower goals for optimal plasma lipid concentrations (Expert Panel, 2001;Grundy et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…Isoflavones are structurally similar to estradiol and have a high binding affinity for the primary estrogen receptors in the vascular wall, estrogen receptor-a and -b (Kuiper et al, 1998;Hodges et al, 2000;Aavik et al, 2001). Several clinical trials have indicated that isoflavones in soy protein may have an important role in lowering serum lipids (Baum et al, 1998;Crouse et al, 1999;Merz-Demlow et al, 2000;Gardner et al, 2001;Clerici et al, 2007). In addition, epidemiologic studies have documented that the Asian populations who consume soy foods as a dietary staple have a lower incidence of CVD than those who consume a typical Western diet (Beaglehole, 1990;Zhang et al, 2003;Sacks et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies conducted in normocholesterolaemic and mildly hypercholesterolaemic women consuming their habitual diets reported that supplementation with isolated soya protein powder (low or high in isoflavones) had no impact on LDL-PPD 24,25 . We have shown in a more recent controlled study that consumption of soya protein produced an important redistribution of LDL from small to larger particles and a significant reduction in the proportion of LDL with a diameter ,25·5 nm (LDL % ,25·5 nm ) 22 .…”
Section: Discussionmentioning
confidence: 99%